Substitusi Parsial Batu Apung Sebagai Agregat Kasar Pada Campuran Beton - Abdul Gaus; Mufti Amir Sultan; Raudha Hakim; Imran Imran; Inggrayani Anggreni waiola (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2020)
This article discusses lightweight concrete that uses pumice as a substitute for a portion of normal coarse aggregate. The pumice used comes from the Rum quarry of North Maluku Tidore Island. Discussion of research results based on the results of testing in the laboratory. The test aims to find out the optimum composition of the use of pumice as a lightweight concrete aggregate. Tests are carried out on cylindrical specimens 15 x 30 cm with pumice composition compared to normal coarse aggregate of 0:100, 25:75, 50:50, 75:25, and 100: 0. The compressive strength test results obtained the optimum composition of pumice substitution at 25% with a compressive strength of 14,72 MPa with the optimum composition. Density of concrete with pumice aggregate which is included in lightweight concrete at a composition of 75% by weight of pumice against normal aggregate with a concrete weight of 1828,73 kg / m3 lighter 14,40% compared to normal concrete.